2018
DOI: 10.1002/jib.497
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation temperature and the phenolic and aroma profile of persimmon wine

Abstract: Persimmon wine may offer nutritional and medicinal value as it contains compounds that may be beneficial to health. Product quality is impacted by fermentation and this study investigated the influence of different fermentation temperatures on the phenolic content, aroma profile and antioxidant activity of persimmon wine. Low ethanol concentration and high residual sugar content were found in wine fermented at low temperature (15°C) leading to sluggish fermentation. The majority of phenolic compounds determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…These results were similar to the study by Liu et al. (2018) in persimmon wine. On the other hand, TPC decreased slightly with an increase in TSS of Burans must from 22 to 26°Bx.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results were similar to the study by Liu et al. (2018) in persimmon wine. On the other hand, TPC decreased slightly with an increase in TSS of Burans must from 22 to 26°Bx.…”
Section: Resultssupporting
confidence: 93%
“…However, when temperature increases from 31 to 34°C and pH increased from 3.50 to 4.30, the TFC of wine increased from 445 to 1,056 mg QE/L. This result was similar with previous researcher (Liu et al., 2018) who observed the maximum TFC at elevated temperature in persimmon wine. The outcoming trend is similar with the study by Eddine et al.…”
Section: Resultssupporting
confidence: 91%
“…Kim et al observed that the production of certain metabolites in tomato vinegar depended on the strain of acetic acid bacteria used and that the fermentation temperature also had a significant influence on the production of such metabolites [45]. Table 3 indicates the mean relative areas of the volatile compounds in the vinegars produced at 30 • C and at 37 • C. It can be observed that most of the volatile compounds reached higher concentration values in the vinegar that had been produced at 30 • C compared to those corresponding to the vinegar produced at 37 • C. According to Liu et al, the aroma compounds and their concentrations were influenced by the fermentation temperature, so that as the temperature was increased, the number of volatiles would decrease [46]. Consequently, certain compounds, such as 1,3-dioxolane, 2,4,5-trimethyl-, 1-hexanol, 3-hexen-1-ol (E), 3-hexen-1-ol (Z), cyclopentene or trans-2-cis-6-nonadienal, would even disappear when the acetic fermentation was conducted at 37 • C. These changes in the concentration of certain compounds could be explained by their possible reduction by evaporation when submitted to high temperatures (37 • C), which, in some cases, might lead to their total disappearance [15].…”
Section: Volatile Compoundsmentioning
confidence: 98%
“…Higher alcohols such as isoamyl alcohol and phenylethyl alcohol are produced in the range of fermentation temperature 15 to 30°C. Besides, esters are the main contributors of fruity aroma and sensory character of wine which are significantly influenced by fermentation temperature [36]. The reason for the change in the sensory property of wine could be due to fermentation temperatureenhanced biomolecules solubility from the fermenting substrate.…”
Section: Total Phenol Content Of the Produced Winementioning
confidence: 99%